Improvements to the Secure Construction and Utilization of Greedy Embeddings in Friend-to-Friend Overlays - Byrenheid, Martin; Roos, Stefanie; Strufe, Thorsten (Electronic Communications of the EASST, 2021)
Routing based on greedy network embeddings enables efficient and privacy-preserving routing in overlays where connectivity is restricted to mutually trusted nodes. In previous works, we proposed security enhancements to the embedding and routing procedures to protect against denial-of-service attacks by malicious overlay participants. In this work, we propose an improved timeout scheme to reduce the stabilization overhead of secure tree maintenance in response to node failures and malicious behavior. Furthermore, we present an attack-resistant packet replication scheme that leverages alternative paths discovered during routing.